The Social Adjustment of British Immigrant Families in Verdun and Pointe-Saint-Charles - Davidson, Mary (Université McGill, 1933)
Keywords: Britanniques; Pointe-Saint-Charles; Quartiers; Verdun

De la contestation à la création, l'usage de l'espace urbain par les mouvements sociaux : le cas du Centre social autogéré de Pointe Saint-Charles - Dussault, Joëlle (Université du Québec à Montréal, 2016)
Keywords: Groupes populaires; Pointe-Saint-Charles; Quartiers

Pointe Saint-Charles: un quartier, des femmes, une histoire communautaire - Le Collectif CourtePointe [Isabelle Drolet et Anna Kruzynski] (Les éditions du remue-ménage, 2006)
Keywords: Femmes; Groupes populaires; Idéologies; Pointe-Saint-Charles; Quartiers

The Keystone of the Neighbourhood: Gender, Collective Action, and Working-Class Heritage Strategy in Pointe-Saint-Charles, Montreal - Hammond, Cynthia Imogen (Journal of Canadian Studies / Revue d'études canadiennes, 2018)
issued: 2018-24-00
Keywords: Casernes; Conservation; Femmes; Groupes populaires; Parcs; Patrimoine; Pointe-Saint-Charles; Quartiers

Long-Term Results of User Participation in Housing Rehabilitation: The Community Design Workshop in Pointe St. Charles - You, Danhui (Université McGill, 1998)
Keywords: Logement; Pointe-Saint-Charles

Factories and Foreigners: Church Life in Working-Class Neighbourhoods in Hamilton and Montreal, 1890-1930 - Gauvreau, Michael (The Churches and Social Order in Nineteenth- and Twentieth-Century Canada, 2006)
Keywords: Pointe-Saint-Charles; Quartiers

Vivre dans un quartier ouvrier de Montréal vers 1930 - Lauzon, Gilles (Histoire Québec, 2017)
Number: 1
Keywords: Pointe-Saint-Charles; Quartiers

Du silence à l'affirmation: Women Making History in Point St. Charles - Kruzynski, Anna (Université McGill, 2004)
Keywords: Femmes; Pointe-Saint-Charles; Quartiers

The City Below the Hill - Ames, Herbert Brown (University of Toronto Press, 1972)
Keywords: Griffintown; Pointe-Saint-Charles; Saint-Antoine; Sainte-Anne

Ferme Saint-Gabriel - Dubé, Patrice (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Congrégation de Notre-Dame; Patrimoine; Pointe-Saint-Charles; Saint-Gabriel (ferme)

An Analysis of the Payrolls of the Point St. Charles Shops of the Grand Trunk Railway - Hoskins, Ralph F. H. (Université McGill, Département de géographie, 1987)
Keywords: Chemins de fer; Grand Tronc; Pointe-Saint-Charles; Quartiers

A Study of the Point St. Charles Shops of the Grand Trunk Railway in Montreal, 1880-1917 - Hoskins, Ralph F. H. (Université McGill, 1987)
Keywords: Chemins de fer; Grand Tronc; Pointe-Saint-Charles; Quartiers

An Analysis of the Payrolls of the Point St. Charles Shops of the Grand Trunk Railway - Hoskins, Ralph F. H. (Cahiers de géographie du Québec, 1989)
Number: 90
Keywords: Chemins de fer; Grand Tronc; Pointe-Saint-Charles; Quartiers

The Point is... Grassroots Organizing Works: Women from Point St. Charles sharing stories of solidarity - Le Collectif CourtePointe [Isabelle Drolet et Anna Kruzynski] (Les éditions du remue-ménage, 2006)
Keywords: Femmes; Groupes populaires; Idéologies; Pointe-Saint-Charles; Quartiers

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (McGill-Queen's University Press, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."–
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail